Cobitis indus, a new spined loach from the Dalaman River in the Eastern Aegean Sea basin (Teleostei: Cobitidae) - Eagderi, Soheil; Secer, Burak; Freyhof, Jörg (Zootaxa, 2022)
Cobitis indus, new species, from the Dalaman River drainage, is distinguished from other Cobitis species in the eastern Aegean Sea basin by having two laminae circularis, a bifurcate suborbital spine, a narrow caudal peduncle, pigmentation zone 4 with 17–24 small blotches often fused into a stripe, pigmentation below Z4 usually absent, and one black, comma-shaped spot at the upper caudal-fin base. It is further distinguished from its closest relative, C. dorademiri, by having 13 diagnostic nucleotide substitutions in the mtDNA COI barcode region and a K2P nearest–neighbour distance of 2.3–2.7%. This is the fourth Cobitis species found in the Dalaman River drainage making this river the most species-rich in spined loaches in the Middle East.